Competency-based Professional Advancement Model for Advanced Practice RNs. (February 2019) - Paul, Fiona; Abecassis, Leah; Freiberger, Dawn; Hamilton, Susan; Kelly, Pamela; Klements, Elizabeth; LaGrasta, Christine; Lemire, Lindsay; O'Donnell, Ellen; Patisteas, Erin; Phinney, Caitlin; Conwell, Karen; et al.
Abstract : The process of developing a 3-tiered advanced practice RN (APRN) competency-based professional advancement model at Boston Children's Hospital is described. The model recognizes the contributions of entry-level and expert APRNs to advanced clinical practice and outcomes, impact, and leadership, while incorporating the tenets of Patricia Benner's Novice to Expert Model and the American Association of Critical- Care Nurses Synergy Model of Care.